Estudo de testes in vitro para predição de fertilidade de machos mamíferos - Corcini, Carine Dahl (2010)
The knowledge of the reproductive potential of a male has economical and reproductive importance, especially if he is used in artificial insemination programs. The conventional assays for evaluating seminal quality do not have the capacity of measuring the fertilizing potential of a sample, they only indicate if it is within the acceptable parameters for insemination, according to the Brazilian College of Animal Reproduction. Into this context, the in vitro sperm penetration assay presents itself as an alternative laboratorial test to categorize fertile males regarding their fecundation capacity, since they mimic in vitro what happens in vivo. However, this assay has its use limited by the difficulty of execution and by the utilization of high cost equipment. The present work aimed to find a new biological model to study male reproductive aspects and to evaluate alternatives to simplify and to decrease costs of the assay execution: use of the chicken egg inner perivitelline layer (IPVL) penetration assay and its association with in vitro and in vivo parameters; use of BTS as incubation media for the in vitro penetration assay, and female gametes cryopreservation using different methods. It was concluded that: 1) Calomys laucha can be used as a biological model; 2) it is possible to use the inner perivitelline layer as a substrate in assays to predict fertility of Calomys laucha males; 3) the IPVL has receptors that allow swine sperm binding, therefore presents potential for use in male fertility diagnostic tests; 4) it is possible to use BTS as incubation media for the in vitro penetration assay, in oocytes or in IPVL, and in water-bath without CO2, and 5) the cryopreservation of ovaries at -20ºC or the refrigeration of oocytes in PBS at 5ºC before the execution of the in vitro oocyte penetration assay, using mTBM media, is an alternative to the use of fresh oocytes in tests to predict swine semen fertility.